HPC / PAM ionic conductive hydrogel as well as preparation method and application thereof

By adding FeCl3 to the HPC/PAM system and combining the characteristics of HPC and PAM, HPC/PAM ion conductive hydrogel was prepared, which solved the problems of flexibility, biocompatibility and single function of flexible sensing materials, and achieved Efficient humidity and temperature sensing effects.

CN119390900AActive Publication Date: 2025-02-07SHAANXI UNIV OF SCI & TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411744017.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-30
Publication Date
2025-02-07
Estimated Expiration
2044-11-30

AI Technical Summary

Technical Problem

In practical applications, existing flexible sensing materials have problems such as insufficient flexibility, poor biocompatibility, single function or delamination of electronic fillers and substrates.

Method used

HPC/PAM ion conductive hydrogel is used as a flexible sensing material. By adding FeCl3 to the HPC/PAM system, ionic conductivity is provided, combining HPC's water retention and PAM's water absorption performance, enhancing the humidity and temperature sensing performance of the material.

Benefits of technology

The good mechanical properties and conductivity of flexible sensors are achieved, the response sensitivity of humidity and temperature sensing is improved, and multiple defects of traditional flexible sensing materials are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390900A_ABST
    Figure CN119390900A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of flexible sensing materials, and discloses an HPC / PAM ionic conductive hydrogel and a preparation method and application thereof.The preparation method comprises the steps that an acrylamide monomer and a hydroxy propyl cellulose solution are mixed, a cross-linking agent and an initiator are added, stirring is conducted, and an HPC / AM solution is obtained; carrying out free radical polymerization reaction on the HPC / AM solution, and standing to obtain HPC / PAM hydrogel; placing the HPC / PAM hydrogel in a FeCl3 solution, soaking the HPC / PAM hydrogel, and carrying out aging treatment to obtain an HPC / PAM ionic conductive hydrogel; the HPC / PAM ionic conductive hydrogel prepared by the invention has good mechanical properties and conductivity; the mechanical temperature and humidity sensor prepared from the HPC / PAM ionic conductive hydrogel has good mechanical properties and high temperature and humidity response sensitivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flexible sensing materials, and in particular relates to a HPC / PAM ion conductive hydrogel and a preparation method and application thereof. Background Art

[0002] Flexible sensors are sensors made of flexible sensing materials. They can perfectly solve the defects of traditional rigid sensing materials (such as semiconductor materials, ceramic materials, etc.), making the sensors more adaptable to different shapes and surfaces, with better wearability and comfort, and can be used for information collection on curved surfaces or under dynamic conditions.

[0003] However, existing flexible sensing materials often have problems such as unsatisfactory flexibility, poor biocompatibility, single function, or delamination of electronic fillers and substrates in practical applications. Summary of the invention

[0004] In view of the technical problems existing in the prior art, the present invention provides a HPC / PAM ion conductive hydrogel and a preparation method and application thereof, so as to solve the technical problems that the existing flexible sensing materials often have insufficient flexibility, poor biocompatibility, single function or delamination of electronic fillers and substrates in practical applications.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is: The present invention provides a method for preparing a HPC / PAM ion conductive hydrogel, comprising: Mixing acrylamide monomer and hydroxypropyl cellulose solution, adding a crosslinking agent and an initiator, and stirring to obtain an HPC / AM solution; The HPC / AM solution is subjected to a free radical polymerization reaction, and after standing, a HPC / PAM hydrogel is obtained; The HPC / PAM hydrogel is placed in a FeCl3 solution, immersed, and aged to obtain the HPC / PAM ion conductive hydrogel.

[0006] Further, the preparation process of the hydroxypropyl cellulose solution is specifically as follows: Hydroxypropyl cellulose is added into preheated deionized water and stirred to disperse, and then transferred to room temperature and stirred to obtain a hydroxypropyl cellulose solution.

[0007] Furthermore, the cross-linking agent is methylenebisacrylamide, and the initiator is ammonium persulfate.

[0008] Further, the HPC / AM solution is subjected to a free radical polymerization reaction, and after standing, a process of obtaining an HPC / PAM hydrogel is specifically as follows: The HPC / AM solution is placed in a mold, free radical polymerized at 60-70° C. for 10-20 h, and then allowed to stand at room temperature for 12-24 h.

[0009] Furthermore, the soaking time is 12-36 hours.

[0010] Furthermore, during the aging process, the aging temperature is 20-30°C, the relative humidity is 65-75%, and the aging time is 12-48h.

[0011] The present invention also provides a HPC / PAM ion conductive hydrogel, and the HPC / PAM ion conductive hydrogel is prepared by using the HPC / PAM ion conductive hydrogel preparation method.

[0012] Furthermore, the HPC / PAM ion conductive hydrogel has a fracture strength of 100-200 KPa and an electrical conductivity of 300-500 Sm -1 , the adhesion is 5-30KPa.

[0013] The present invention also provides an application of an HPC / PAM ion conductive hydrogel, characterized in that the HPC / PAM ion conductive hydrogel is used as a flexible sensing material to prepare a flexible sensor.

[0014] Furthermore, the stress-strain sensing current change rate of the flexible sensor is 80%-110%, the humidity sensing current change rate is 10%-20%, and the temperature response range is 10-60°C.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The HPC / PAM ion conductive hydrogel provided by the present invention and its preparation method and application, select HPC with excellent water solubility and good biocompatibility as the temperature and humidity sensitive material of the sensor, use PAM as a transparent flexible hydrogel, add FeCl3 in the HPC / PAM system to provide ion conductivity, the hydrogel prepared by PAM has good water absorption performance, stability and transparency, the HPC material has excellent water retention, the humidity sensing performance of the hydrogel is enhanced by the multi-hydroxyl groups on its surface, the temperature sensing performance of reducing the transparency of the material at high temperature is achieved by the low critical solution temperature, and the output of the sensing signal is achieved by the good ion conductivity brought by FeCl3; during the preparation process, HPC is evenly distributed in the hydrogel in the form of a mesh, which brings better humidity sensing sensitivity compared with other hydrogels, and HPC can exist in the hydrogel matrix in the form of an aqueous solution, while enhancing the humidity sensitive performance, it does not affect other properties of the material such as mechanical properties, transparency, etc.; the HPC / PAM ion conductive hydrogel prepared by the present invention has good mechanical properties and conductive properties; the mechanical, temperature and humidity sensors prepared by using the HPC / PAM ion conductive hydrogel have good mechanical properties and high temperature and humidity response sensitivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0017] Figure 1 This is a SEM image of the HPC / PAM ion conductive hydrogel prepared in Example 5 magnified 2000 times; Figure 2 This is a SEM image of the HPC / PAM ion conductive hydrogel prepared in Example 5, magnified 10,000 times. DETAILED DESCRIPTION

[0018] In order to make the technical problems, technical solutions and beneficial effects solved by this application clearer, the technical solutions in the embodiments of this application will be described clearly and completely in combination with the drawings in the embodiments of this application; obviously, the described embodiments are only part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0019] The present invention provides a method for preparing a HPC / PAM ion conductive hydrogel, comprising the following steps: Step 1: Add HPC to deionized water preheated to 60°C and disperse it by mechanical stirring for 15-60 minutes, then transfer it to room temperature and stir it for 6-24 hours to obtain a HPC solution with a mass fraction of 0.5%-10%.

[0020] Step 2: Add 4-10 g of acrylamide monomer (AM) to 10-40 g of the HEC solution, and add 0.0025-0.05 g of methylenebisacrylamide (MBA) and 0.01-0.2 g of ammonium persulfate (APS) in sequence, and stir at room temperature for 1-3 hours to obtain an HPC / AM solution; wherein methylenebisacrylamide is used as a cross-linking agent and ammonium persulfate is used as an initiator.

[0021] Step 3: Place 10-40 g of the HPC / AM solution in a polytetrafluoroethylene mold with a diameter of 8-15 cm, perform free radical polymerization at 60-70° C. for 10-20 h, and then stand at room temperature for 12-24 h to obtain an HPC / PAM hydrogel.

[0022] Step 4: Add 25-100 g of ferric chloride hexahydrate to 100-1000 ml of deionized water and stir at room temperature for 2-6 hours to obtain a FeCl3 solution.

[0023] Step 5: Cut the HPC / PAM hydrogel into a rectangle with a length of 2-5 cm and a width of 1-4 cm, place it in a 100 mL beaker, add 20-40 mL of the FeCl3 solution, soak for 12-36 h, and then age it at 20-30 ° C and 65-75% RH for 12-48 h to prepare the HPC / PAM ion conductive hydrogel.

[0024] Preparation principle: The preparation method of the HPC / PAM ion conductive hydrogel of the present invention adopts HPC as a temperature and humidity sensitive material of the sensor, uses PAM as a transparent flexible hydrogel, and adds FeCl3 to the HPC / PAM system to provide ionic conductivity, and combines the excellent water retention of FeCl3 and HPC / PAM to provide stable ionic conductivity for the HPC / PAM hydrogel; specifically, the hydrogel prepared by PAM has good water absorption performance, stability and transparency, the HPC material has excellent water retention, the humidity sensing performance of the hydrogel is enhanced by the multi-hydroxyl groups on its surface, the temperature sensing performance of reducing the transparency of the material at high temperature is achieved by the low critical solution temperature, and the output of the sensing signal is achieved by the good ionic conductivity brought by FeCl3; during the preparation process, HPC is evenly distributed in the hydrogel in a mesh form, which brings better humidity sensing sensitivity compared with other hydrogels, and HPC can exist in the hydrogel matrix in the form of an aqueous solution, while enhancing the humidity sensitive performance, it does not affect other properties of the material such as mechanical properties and transparency.

[0025] The HPC / PAM ion conductive hydrogel prepared by the present invention has good mechanical properties and electrical conductivity; wherein the HPC / PAM ion conductive hydrogel has a fracture strength of 100-200 KPa and an electrical conductivity of 300-500 Sm -1 , the adhesion is 5-30KPa; the mechanical, temperature and humidity sensors prepared with HPC / PAM ion conductive hydrogel have good mechanical properties and high temperature and humidity response sensitivity; among them, the stress strain sensing current change rate is as high as 80%~110%, the humidity sensing current change rate is as high as 10%-20%, and the temperature response range is 10-60℃.

[0026] Example 1 This embodiment 1 provides a method for preparing a HPC / PAM ion conductive hydrogel, comprising the following steps: Step 1: Add HPC to deionized water preheated to 60°C and disperse it by mechanical stirring for 15 minutes, then transfer it to room temperature and stir for 6 hours to obtain a 0.5% HPC solution.

[0027] Step 2: Add 4 g of acrylamide monomer (AM) to 10 g of the HEC solution, and then add 0.0025 g of methylenebisacrylamide (MBA) and 0.01 g of ammonium persulfate (APS), and stir at room temperature for 1 h to obtain an HPC / AM solution.

[0028] Step 3: Place 10 g of the HPC / AM solution in a polytetrafluoroethylene mold with a diameter of 8 cm, subject it to free radical polymerization at 60° C. for 10 h, and then allow it to stand at room temperature for 12 h to obtain an HPC / PAM hydrogel.

[0029] Step 4: Add 25 g of ferric chloride hexahydrate into 100 ml of deionized water and stir at room temperature for 2 h to obtain a FeCl3 solution.

[0030] Step 5: Cut the HPC / PAM hydrogel into a rectangle with a length of 2 cm and a width of 1 cm, place it in a 100 mL beaker, add 20 mL of the FeCl3 solution, soak for 12 h, and then age it at 30°C and 70% RH for 12 h to prepare the HPC / PAM ion conductive hydrogel.

[0031] The HPC / PAM ion conductive hydrogel prepared in Example 1 has a fracture strength of 100 KPa and an electrical conductivity of 450 Sm -1, the adhesion is 5KPa; the mechanical, temperature and humidity sensors prepared with HPC / PAM ion conductive hydrogel have good mechanical properties and high temperature and humidity response sensitivity; among them, the stress strain sensing current change rate is as high as 88%, the humidity sensing current change rate is as high as 15%, and the temperature response range is 10-60℃.

[0032] Example 2 This embodiment 2 provides a method for preparing a HPC / PAM ion conductive hydrogel, comprising the following steps: Step 1: Add HPC to deionized water preheated to 60°C and disperse it by mechanical stirring for 60 minutes, then transfer it to room temperature and stir it for 24 hours to obtain a 10% HPC solution.

[0033] Step 2: Add 10 g of acrylamide monomer (AM) to 40 g of the HEC solution, and then add 0.05 g of methylenebisacrylamide (MBA) and 0.2 g of ammonium persulfate (APS), and stir at room temperature for 3 h to obtain an HPC / AM solution.

[0034] Step 3: Place 40 g of the HPC / AM solution in a polytetrafluoroethylene mold with a diameter of 15 cm, subject it to free radical polymerization at 70° C. for 20 h, and then allow it to stand at room temperature for 24 h to obtain an HPC / PAM hydrogel.

[0035] Step 4: Add 100 g of ferric chloride hexahydrate into 1000 ml of deionized water and stir at room temperature for 6 h to obtain a FeCl3 solution.

[0036] Step 5: Cut the HPC / PAM hydrogel into a rectangle of 5 cm in length and 4 cm in width, place it in a 100 mL beaker, add 40 mL of the FeCl3 solution, soak for 36 h, and then age it at 20 ° C and 75% RH for 12 h to prepare the HPC / PAM ion conductive hydrogel.

[0037] The HPC / PAM ion conductive hydrogel prepared in Example 2 has a fracture strength of 180 KPa and an electrical conductivity of 370 Sm -1 , the adhesion is 30KPa; the mechanical, temperature and humidity sensors prepared with HPC / PAM ion conductive hydrogel have good mechanical properties and high temperature and humidity response sensitivity; among them, the stress strain sensing current change rate is as high as 82%, the humidity sensing current change rate is as high as 18%, and the temperature response range is 10-60℃.

[0038] Example 3 This embodiment 3 provides a method for preparing a HPC / PAM ion conductive hydrogel, comprising the following steps: Step 1: Add HPC to deionized water preheated to 60°C and disperse it by mechanical stirring for 40 minutes, then transfer it to room temperature and stir it for 12 hours to obtain a 2% HPC solution.

[0039] Step 2: Add 6 g of acrylamide monomer (AM) to 20 g of the HEC solution, and then add 0.01 g of methylenebisacrylamide (MBA) and 0.05 g of ammonium persulfate (APS), and stir at room temperature for 2 h to obtain an HPC / AM solution.

[0040] Step 3: Place 20 g of the HPC / AM solution in a polytetrafluoroethylene mold with a diameter of 10 cm, subject it to free radical polymerization at 60° C. for 14 h, and then allow it to stand at room temperature for 12 h to obtain an HPC / PAM hydrogel.

[0041] Step 4: Add 50 g of ferric chloride hexahydrate into 1000 ml of deionized water and stir at room temperature for 4 h to obtain a FeCl3 solution.

[0042] Step 5: Cut the HPC / PAM hydrogel into a rectangle with a length of 4 cm and a width of 2 cm, place it in a 100 mL beaker, add 30 mL of the FeCl3 solution, soak for 24 h, and then age it at 25 ° C and 70% RH for 24 h to prepare the HPC / PAM ion conductive hydrogel.

[0043] The HPC / PAM ion conductive hydrogel prepared in Example 3 has a fracture strength of 140 KPa and a conductivity of 400 Sm -1 , the adhesion is 24KPa; the mechanical, temperature and humidity sensors prepared with HPC / PAM ion conductive hydrogel have good mechanical properties and high temperature and humidity response sensitivity; among them, the stress strain sensing current change rate is as high as 97%, the humidity sensing current change rate is as high as 16%, and the temperature response range is 10-60℃.

[0044] Example 4 This embodiment 4 provides a method for preparing a HPC / PAM ion conductive hydrogel, comprising the following steps: Step 1: Add HPC to deionized water preheated to 60°C and disperse it by mechanical stirring for 40 minutes, then transfer it to room temperature and stir it for 20 hours to obtain a 5% HPC solution.

[0045] Step 2: Add 8 g of acrylamide monomer (AM) to 30 g of the HEC solution, and then add 0.0055 g of methylenebisacrylamide (MBA) and 0.05 g of ammonium persulfate (APS), and stir at room temperature for 2 h to obtain an HPC / AM solution.

[0046] Step 3: Place 30 g of the HPC / AM solution in a polytetrafluoroethylene mold with a diameter of 12 cm, subject it to free radical polymerization at 65° C. for 18 h, and then allow it to stand at room temperature for 12 h to obtain an HPC / PAM hydrogel.

[0047] Step 4: Add 70 g of ferric chloride hexahydrate into 500 ml of deionized water and stir at room temperature for 5 h to obtain a FeCl3 solution.

[0048] Step 5: Cut the HPC / PAM hydrogel into a rectangle with a length of 4 cm and a width of 3 cm, place it in a 100 mL beaker, add 35 mL of the FeCl3 solution, soak for 30 h, and then age it at 20 ° C and 70% RH for 24 h to prepare the HPC / PAM ion conductive hydrogel.

[0049] The HPC / PAM ion conductive hydrogel prepared in Example 4 has a fracture strength of 120 KPa and a conductivity of 500 Sm -1 , the adhesion is 19KPa; the mechanical, temperature and humidity sensors prepared with HPC / PAM ion conductive hydrogel have good mechanical properties and high temperature and humidity response sensitivity; among them, the stress strain sensing current change rate is as high as 80%, the humidity sensing current change rate is as high as 10%, and the temperature response range is 10-60℃.

[0050] Example 5 This embodiment 5 provides a method for preparing a HPC / PAM ion conductive hydrogel, comprising the following steps: Step 1: Add HPC to deionized water preheated to 60°C and disperse it by mechanical stirring for 30 minutes, then transfer it to room temperature and stir it for 18 hours to obtain a 1% HPC solution.

[0051] Step 2: Add 6 g of acrylamide monomer (AM) to 20 g of the HEC solution, and then add 0.02 g of methylenebisacrylamide (MBA) and 0.08 g of ammonium persulfate (APS), and stir at room temperature for 1.5 h to obtain an HPC / AM solution.

[0052] Step 3: Place 20 g of the HPC / AM solution in a polytetrafluoroethylene mold with a diameter of 9 cm, subject it to free radical polymerization at 60° C. for 20 h, and then allow it to stand at room temperature for 20 h to obtain an HPC / PAM hydrogel.

[0053] Step 4: Add 30 g of ferric chloride hexahydrate into 500 ml of deionized water and stir at room temperature for 3 h to obtain a FeCl3 solution.

[0054] Step 5: Cut the HPC / PAM hydrogel into a rectangle with a length of 3 cm and a width of 2 cm, place it in a 100 mL beaker, add 28 mL of the FeCl3 solution, soak for 32 h, and then age it at 25 ° C and 70% RH for 20 h to prepare the HPC / PAM ion conductive hydrogel.

[0055] The HPC / PAM ion conductive hydrogel prepared in Example 4 has a fracture strength of 170 KPa and an electrical conductivity of 320 Sm -1 , the adhesion is 12KPa; the mechanical, temperature and humidity sensors prepared with HPC / PAM ion conductive hydrogel have good mechanical properties and high temperature and humidity response sensitivity; among them, the stress strain sensing current change rate is as high as 110%, the humidity sensing current change rate is as high as 20%, and the temperature response range is 10-60℃.

[0056] As attached Figure 1-2 As shown, attached Figure 1 The SEM image of the HPC / PAM ion conductive hydrogel prepared in Example 5 is given in the attached Figure 2 The SEM image of the HPC / PAM ion conductive hydrogel prepared in Example 5 is given in FIG. Figure 1-2 It can be seen that HPC is evenly distributed inside the composite hydrogel and forms a network structure, and the addition of HPC has no effect on the structure of PAM.

[0057] The HPC / PAM ion conductive hydrogel and its preparation method and application described in the present invention, HPC is evenly distributed in the hydrogel in a mesh form, which brings better humidity sensing sensitivity compared with other hydrogels, and HPC can exist in the hydrogel matrix in the form of an aqueous solution. While enhancing the humidity sensitive performance, it does not affect other properties of the material such as mechanical properties and transparency; FeCl3 is added to the HPC / PAM system, and combined with the excellent water retention of the two, a stable ion conductivity is provided for the HPC / PAM hydrogel. By using PAM as a matrix, HPC as a temperature and humidity sensitive component, and FeCl3 as a conductive component, a flexible sensor material with stress strain sensing and temperature and humidity sensing capabilities is prepared.

[0058] The above embodiment is only one of the implementation methods that can realize the technical solution of the present invention. The scope of protection claimed by the present invention is not limited only to this embodiment, but also includes changes, replacements and other implementation methods that can be easily thought of by any technician familiar with the technical field within the technical scope disclosed by the present invention.

Claims

1. A method for preparing HPC / PAM ion conductive hydrogel, characterized in that: include: Mixing acrylamide monomer and hydroxypropyl cellulose solution, adding a crosslinking agent and an initiator, and stirring to obtain an HPC / AM solution; The HPC / AM solution is subjected to a free radical polymerization reaction, and after standing, a HPC / PAM hydrogel is obtained; The HPC / PAM hydrogel is placed in a FeCl3 solution, immersed, and aged to obtain the HPC / PAM ion conductive hydrogel.

2. The method for preparing a HPC / PAM ion conductive hydrogel according to claim 1, characterized in that: The preparation process of hydroxypropyl cellulose solution is as follows: Hydroxypropyl cellulose is added into preheated deionized water and stirred to disperse, and then transferred to room temperature and stirred to obtain a hydroxypropyl cellulose solution.

3. The method for preparing a HPC / PAM ion conductive hydrogel according to claim 1, characterized in that: The cross-linking agent is methylenebisacrylamide, and the initiator is ammonium persulfate.

4. The method for preparing a HPC / PAM ion conductive hydrogel according to claim 1, characterized in that: The HPC / AM solution is subjected to a free radical polymerization reaction, and after standing, a process of obtaining an HPC / PAM hydrogel is specifically as follows: The HPC / AM solution is placed in a mold, free radical polymerized at 60-70° C. for 10-20 h, and then allowed to stand at room temperature for 12-24 h.

5. The method for preparing a HPC / PAM ion conductive hydrogel according to claim 1, characterized in that: The soaking time is 12-36h.

6. The method for preparing a HPC / PAM ion conductive hydrogel according to claim 1, characterized in that: During the aging process, the aging temperature is 20-30°C, the relative humidity is 65-75%, and the aging time is 12-48h.

7. A HPC / PAM ion conductive hydrogel, characterized in that: The HPC / PAM ion conductive hydrogel is prepared by the preparation method of the HPC / PAM ion conductive hydrogel according to claims 1-6.

8. The HPC / PAM ion conductive hydrogel according to claim 7, characterized in that: The HPC / PAM ion conductive hydrogel has a fracture strength of 100-200 KPa and an electrical conductivity of 300-500 Sm -1 , the adhesion is 5-30KPa.

9. The use of a HPC / PAM ion conductive hydrogel as claimed in claim 7 or 8, characterized in that: The HPC / PAM ion conductive hydrogel is used as a flexible sensing material to prepare a flexible sensor.

10. The use of a HPC / PAM ion conductive hydrogel according to claim 9, characterized in that: The stress-strain sensing current change rate of the flexible sensor is 80%-110%, the humidity sensing current change rate is 10%-20%, and the temperature response range is 10-60°C.

Citation Information

Patent Citations

  • Preparation method for hydroxyethyl cellulose / polyacrylamide hydrogel with high stretchability

    CN107973881A

  • Stretchable conductive hydrogel with high water-retaining property and preparation method thereof

    CN113416318A

  • Heat-sensitive gel material for intelligent window and preparation method of heat-sensitive gel material

    CN114573756A

  • Synthesis method and application of temperature-sensitive intelligent hydrogel based on PNIPAm-HPC

    CN114672043A

  • Hydrogel electrolyte and preparation method and application thereof

    CN116836338A